Rodziny literackie w Rosji czasów Oświecenia (trzy przykłady) - Dąbrowska, Magdalena (Rusycystyczne Studia Literaturoznawcze, 2016)
The article consists of five parts: 1. Preface (the literary families and a development of the literary institutions — periodicals, literary circles etc.), 2. Father and daughter (Alexander Sumarokov and Ekaterina Sumarokova‑Knyazhnina) (the poems in the periodical “Trudolubiwaya ptchela”, P. Berkov and G. Gukovskyi polemics), 3. Sisters (Alexandra Magnickaya and Natalia Magnickaya) (the translation of the Letters on Italy by Ch. Dupaty), 4. Wife and husband (Mikhail Kheraskov and Elizaveta Kheraskova) (the literary school of Kheraskov, the periodicals by Kheraskov), 5. Conclusion. The article concerns the history of the Russian literature from the sixties to the nineties of the 18th century.